3D printed zirconia used as dental materials: a critical review - Guanyu Su; Yushi Zhang; Chunyu Jin; Qiyue Zhang; Jiarui Lu; Zengqian Liu; Qiang Wang; Xue Zhang; Jia Ma (Journal of Biological Engineering, 2023)
Abstract In view of its high mechanical performance, outstanding aesthetic qualities, and biological stability, zirconia has been widely used in the fields of dentistry. Due to its potential to produce suitable advanced configurations and structures for a number of medical applications, especially personalized created devices, ceramic additive manufacturing (AM) has been attracting a great deal of attention in recent years. AM zirconia hews out infinite possibilities that are otherwise barely possible with traditional processes thanks to its freedom and efficiency. In the review, AM zirconia’s physical and adhesive characteristics, accuracy, biocompatibility, as well as their clinical applications have been reviewed. Here, we highlight the accuracy and biocompatibility of 3D printed zirconia. Also, current obstacles and a forecast of AM zirconia for its development and improvement have been covered. In summary, this review offers a description of the basic characteristics of AM zirconia materials intended for oral medicine. Furthermore, it provides a generally novel and fundamental basis for the utilization of 3D printed zirconia in dentistry.